The risks of self-medication in the elderly affected by coronaviruses and other respiratory syndromes (Research, Society and Development, 2020)
The present study aimed to describe the main risks of self-medication in elderly people affected by coronavirus and other respiratory syndromes. The present study is an exploratory research of the literature review type. For the development of this review, the following steps were taken: 1) definition of the theme and formulation of the guiding question, 2) establishment of inclusion and exclusion criteria, 3) definition of descriptors, 4) pre-selection of articles, 5) evaluation studies (interpretation of results) and 6) presentation of the review. The searches were carried out between February and April 2020, using the Scielo, Science Direct, Google scholar and PubMed databases, with the time frame from 2016 to 2020. The descriptors used, in an associated and isolated way, were: Risk, Elderly, Self-medication, Coronavirus and Respiratory syndrome, in English, Spanish and Portuguese and indexed in DeCS. Within the searches, 488 articles were found; however, after the exclusion of duplicate findings (161), unavailable in full (77) and incomplete (138), they were restricted to 112 works, these were read individually by the researchers. At the end of the analysis, 16 articles were used in the review, which had the descriptors included in the theme and / or summary and were included because they best fit the proposed objective. Self-medication requires special attention in the elderly, as this age group presents a greater risk of drug interactions, with a possible increase in adverse reactions to medications, thus being able to cause complications to patients, mainly due to the typical changes in the aging process.